2002
DOI: 10.1002/ijc.10782
|View full text |Cite
|
Sign up to set email alerts
|

An association of Bcl‐2 phosphorylation and Bax localization with their functions after hyperthermia and paclitaxel treatment

Abstract: Apoptosis is induced by many kinds of therapy-related inducers, such as hyperthermia and chemotherapeutic agents. However, differences in apoptotic pathways between these inducers remain unclear, although knowing the differences is important to map out a therapeutic strategy. Therefore, we focused on the localization and phosphorylation of Bcl-2 and Bax, key mediators of the apoptotic pathway, after hyperthermia and paclitaxel treatment of PC-10 squamous cell carcinoma cells that excessively expressed Bcl-2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 37 publications
0
47
1
Order By: Relevance
“…There is a large literature on this topic, but no clear and general answers have emerged. We were also unable to obtain a clear-cut answer thus far, and our data failed to support some previous suggestions (19)(20)(21). We did confirm that two stressactivated protein kinase pathways, JNK and p38, both previously implicated in paclitaxel-induced cell death (22)(23)(24), were activated by antimitotics, and to some extent, the degree of activation correlated with drug sensitivity.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…There is a large literature on this topic, but no clear and general answers have emerged. We were also unable to obtain a clear-cut answer thus far, and our data failed to support some previous suggestions (19)(20)(21). We did confirm that two stressactivated protein kinase pathways, JNK and p38, both previously implicated in paclitaxel-induced cell death (22)(23)(24), were activated by antimitotics, and to some extent, the degree of activation correlated with drug sensitivity.…”
Section: Discussioncontrasting
confidence: 88%
“…However, a few studies reported death by poorly understood caspase-independent mechanisms (17,18). Inactivation of antiapoptotic proteins Bcl2 and Bcl-xL by phosphorylation was implicated in death triggered by paclitaxel (19,20), as were several kinases, including c-Jun NH 2 terminal kinase (JNK), extracellular signal-regulated kinase (ERK), p38 mitogen activated protein (MAP) kinase, AKT, and protein kinase A (21-26). There are contradictory reports regarding the role of the spindle assembly checkpoint in mediating cell death triggered by antimitotics.…”
Section: Introductionmentioning
confidence: 99%
“…18 In vitro BCL2 protein is known to be slightly downregulated in tumor cells immediately after heat stress (180 minutes, 42.5°C). 15,16 Contrarily, the treatment of human colorectal tumor (RKO.C) and isogenic RC10.1 cells to lower temperatures such as 1 hour at 42°C (water bath hyperthermia) did not reveal any changes in BCL2 expression. 17 Presumably, faster and more direct heat generation in tumor tissues (magnetic heating vs water bath hyperthermia) as well as a distinct threshold of temperature dosage is required for a reduction of BCL2 expression, which is readily provided by the utilization of thermoablative stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…[15][16][17][18] In general, the expression of BCL2, FGF-R1, and HSP70 has been mainly elucidated in connection with hyperthermic temperatures up to 43°C only.…”
Section: 13mentioning
confidence: 99%
“…Therefore, cells treated with taxol are unable to proceed normally through the cell cycle and are arrested in the G 1 and G 2 /M phases (3)(4)(5). During the last decade, additional activities of taxol have been described including 1) its effect on cell signaling and gene expression, activation of mitogen-activated protein kinases, Raf-1, proteintyrosine kinases, and c-Jun NH 2 -terminal kinase (6 -11), and 2) its effect on triggering apoptosis by caspase-dependent and independent pathways (12)(13)(14)(15) as well as necrosis (16) and regulating the expression of apoptosis-related proteins like Bcl-2, Bad, Bcl-xL, p21 WAF-1/CIP-1 , tumor necrosis factor-␣ (TNF-␣) receptor 1 (TNFR1), and the tumor necrosis factorrelated apoptosis-inducing ligand (TRAIL) receptors DR4 and DR5 (17)(18)(19)(20)(21)(22). Up-regulation of the transcription factor FoxO3a by taxol in MCF-7 breast cancer cells can also result in increased levels of Bim, a proapoptotic BH3-only Bcl-2 family member, which can cause apoptosis in these cells (23).…”
Section: From the Department Of Pharmacology And Toxicology And Indiamentioning
confidence: 99%